2015
DOI: 10.5698/1535-7511-15.6.335
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination Triggers, Rather than Causes, Seizures

Abstract: In Clinical Science Commentary Controversy has long surrounded whether vaccination causes seizures and encephalopathy in infants and children (1). The implications of causative claims have been profound with antivaccination lobby groups gaining ground in public debate by sowing seeds of concern in the minds of anxious parents. This fear of vaccination has fueled preventable outbreaks of disease such as measles in developed countries escalating from 40 cases in France in 2006 to >22,000 cases during 2008-2011 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Whether immunological processes such as vaccinations might trigger the onset and occurrence of paroxysmal events including epileptic seizures is still under debate. 17 In our cohort, several triggers of EA episodes were identified (Tables 1 and 2). These included sensory stimuli, e.g., a sudden noise and vibrations of the body.…”
Section: Episodic Ataxia: Phenotypementioning
confidence: 99%
“…Whether immunological processes such as vaccinations might trigger the onset and occurrence of paroxysmal events including epileptic seizures is still under debate. 17 In our cohort, several triggers of EA episodes were identified (Tables 1 and 2). These included sensory stimuli, e.g., a sudden noise and vibrations of the body.…”
Section: Episodic Ataxia: Phenotypementioning
confidence: 99%
“…It is thought that the immune response activated by vaccination triggered a seizure without necessarily producing a high fever or even a fever at all. 37…”
Section: Combinations Of Vaccines and Risk Of Seizuresmentioning
confidence: 99%
“…The longterm rate of epilepsy was not increased in children who had FS following MMR vaccination compared with children who had FS of a different etiology. 37…”
Section: The Risk Of Fs Should Not Obscure the Benefits Of Vaccinationmentioning
confidence: 99%
“…In some studies of epilepsy onset after vaccination, genetic or structural etiologies were found in most children with onset of epilepsy around the time of vaccination, supporting the view of vaccinations as possible precipitating factors of first seizures in susceptible children, rather than as primary, causal factors. 31,32 In several studies, authors conclude that pandemic vaccination may influence the risk of other neurologic conditions, such as Guillain-Barré syndrome, encephalopathies, and narcolepsy, 6 -9 suggesting there is a potential influence on the brain when the immune system has been triggered by vaccination. 37,38 However, no association with narcolepsy was found in a study of a nonadjuvanted pandemic influenza vaccine used in the United States.…”
mentioning
confidence: 99%